Qoheleth: A book in a changing society - Schoors, Antoon (Old Testament essays, 1996)
On the basis of historical allusions in Ecclesiastes 4:13-16, 9:13-16, 10:16-17, the post-exilic date of Qoheleth can be narrowed to the third century BC. With that date in mind the paper deals with the question of how Qoheleth reacts to the socio-political situation of his day. This situation was linked with Ptolemaic rule over Palestine and is characterised by stem administration, an efficient state economy and high taxes. At the social level it created an opposition between the hellenised upper-class and the poor supporters of the Torah. Qoheleth is aware of that political and socio-economic situation and of the stress it imposes on people. However, he does not really criticise these abuses. In his reflections they are not a problem in their own right but they only illustrate the absurdity of human existence.